2011
DOI: 10.1159/000327376
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous T-Cell/Histiocyte-Rich B-Cell Lymphoma: A Case Report and Review of the Literature

Abstract: Background: T-cell/histiocyte-rich large B-cell lymphoma (THRLBCL) primarily presenting on the skin is an extremely rare entity with only sporadic cases reported in the literature. Methods: We here report an extraordinary case of primary cutaneous THRLBCL with self-healing and 24 months of follow-up. Results: The lesion was a dermohypodermal/subcutaneous circumscribed ulcerated nodosity. Histological examination with immunohistochemical, molecular analysis and comparative genomic hybridization were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…T/HRBCL is a nodal disease, but extralnodal sites, such as spleen, liver and bone marrow can be involved[10-12,20,21]. In recent reports, primary cutaneous[22], thyroid[23], thymus[24], and gastrointestinal presentations[25,26] of T/HRBCL were also described. To date, pancreatic involvement of T/HRBCL has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…T/HRBCL is a nodal disease, but extralnodal sites, such as spleen, liver and bone marrow can be involved[10-12,20,21]. In recent reports, primary cutaneous[22], thyroid[23], thymus[24], and gastrointestinal presentations[25,26] of T/HRBCL were also described. To date, pancreatic involvement of T/HRBCL has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Classical Hodgkin lymphoma can also resemble T-cell / histiocyte-rich large B-cell lymphoma or peripheral Tcell lymphoma [35]. For these reasons, fine needle aspiration cytology (FNAC) is considered less accurate for the diagnosis of Hodgkin lymphoma than it is for non-Hodgkin lymphoma [36].…”
Section: Issn-2321-127xmentioning
confidence: 99%
“…In addition, Kodama et al reported previously that LBCL-o showed a better prognosis compared with other subtypes of LBCLs. THRLBCL is categorized as a variant of LBCL-o, and is known to have a relatively good prognosis (1,4). Cutaneous Hodgkin's lymphoma, which ir required for a diagnosis of THRLBL, was excluded based on a negative result for CD15 immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell/histiocyte-rich Large B-cell lymphoma (THRLB-CL) presenting primarily on the skin is an extremely rare entity (1). THRLBCL is considered a subtype of diffuse large B-cell lymphoma, and is characterized by a limited number of scattered, large, atypical B cells embedded in a background of abundant T cells and histiocytes (1). In general, THRLBCL mainly affects the lymph nodes and often presents as stage IV disease.…”
mentioning
confidence: 99%